Mechanical Performance of Direct Restorative Techniques Utilizing Long Fibers for "Horizontal Splinting" to Reinforce Deep MOD Cavities-An Updated Literature Review - Jakab András; Volom András; Sáry Tekla; Vincze-Bandi Eszter; Braunitzer Gábor; Alleman David; Garoushi Sufyan; Fráter Márk (United Kingdom, 2022)
Excessive cavity preparation and root canal treatment leads to a weakened tooth structure with a lower resistance to fracture. Fiber reinforcement is frequently used to reinforce such teeth, and multiple fiber types and possible applications exist. Various methods for utilizing long fibers to internally splint the remaining cavity walls in the case of large mesio-occluso-distal (MOD) cavities have been proposed; however, no summary of their performance has been written up to now. Our study aims to review the available literature to evaluate and compare the mechanical performance of the different materials and methods utilized for horizontal splinting in large MOD cavities. Three independent authors performed a thorough literature search using PubMed, ScienceDirect, and Google Scholar up until January 2022. The authors selected in vitro studies that used long fibers placed horizontally in posterior teeth with large MOD cavities to reinforce these teeth. From 1683 potentially relevant articles, 11 publications met our inclusion criteria. Seven out of eleven studies showed that horizontal splinting with long fibers improved the fracture resistance of the restored teeth. Three articles showed no significant difference between the fracture resistance of the restored groups. Only one article reported a lower fracture resistance to the horizontally splinted group, compared to conventional direct composite restoration. Within the limitations of this review, evidence suggests that long fiber reinforcement could be used to improve the fracture resistance of heavily restored teeth.